Clinical Microbiology: where do we stand? - Vatopoulos, Alkiviadis (Frontiers in Antibiotics, 2024)
Clinical Microbiology has developed during the last 150 simultaneously with the discovery of microorganisms as causes of infections. Globalization and One health determine present needs whereas molecular biology, automation, Artificial intelligence and bioinformatics are new tools that characterize the new developments in the field